Professional practices and perception towards rational use of medicines according to WHO methodology in United Arab Emirates - Abdul Rasool BK; Fahmy SA; Abu-Gharbieh EF; Ali HS (Centro de Investigaciones y Publicaciones Farmaceuticas, 2010)
Inappropriate prescribing reduces the quality of medical care and leads to a waste of resources. No study has been reported concerning rational drug use in United Arab Emirates, UAE, recently. Objectives: 1. assessing patterns of use and defining problems regarding the rational drug use. 2. Setting baseline situational analysis study for practices in the health care system relevant to drug use. Method: A descriptive pilot study, consisting of pharmacists, physicians and patients (100 of each of category) from four private hospitals, (12) medical clinics, (80) community pharmacies in addition to 150 prescriptions. A questionnaire of three sections was designed to include WHO indicators regarding patients, facility and prescribing patterns that are relevant to rational drug use was carried out in four emirates of the UAE in the period December 2008-Febreuary 2009.Results: Consultation and dispensing times were 10 (SD=2.75) min and 68 (SD=9.7) seconds, respectively. Average no. of drugs per prescription was (2.9 + 0.97), % of prescriptions using generic name (7.35%), % of antibiotic containing prescriptions (31.1%), % of injection containing prescriptions (2.9%), adherence to Standard Treatment Protocols (46%), adherence to the essential drug list (64%), patient's knowledge of correct dosage (55%), adequately labeled drugs (45%), patient's information (65%). Conclusions: Several areas of deficiency in rational drug use had been defined in the private sector through UAE that can be remedied through adopting several strategies such as adherence to national standard treatment guidelines and essential drug list based on treatments of choice, interaction between health care system and providing drugs information to consumers.